Validation Method Rapid Test COD in Water and Waste Water compare with Standard Method as Quality Asurance in Integrated Testing Laboratory-FMIPA of Sriwijaya University - Yuniar Yuniar; Maria Siswi Wijayanti (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2020)
Portable COD test kit used for testing the COD because its low cost, less waste, contaminant free, efficient, simple and traceable to the international unit system. However the method has not yet accepted as a standard method, so it must be validated before applied in the laboratory according to the requirements of ISO / IEC 17025: 2017. In this study, the Rapid Test COD method vario Lovibond (M1) compared with the standard method APHA 5220D.4 (M2). The Rapid Test method modified used APHA reagents (M3) and vice versa (M4) were also studied. Evaluation based on precision values,  HorRat  whereas accuracy based on recovery value (R). Comparison of test results also conducted against Certified Reference Material values, and Z-score test. The precision test results for each method for both law range and high range gave HorRat values between 0.3-1.3 that meet the precision requirements. Accuracy testing also gave %R meeting the acceptance limit, even though M3 with the lowest %R is 94.17%. For comparison of results with CRM, the M3 method does not meet the acceptance limit, which is U∆ < ∆m. But the results of the Z-score Test all methods provide satisfactory accuracy